Effect Of Commercial Biofertilizer Product Of Seaweed (Euchema Cottonii) Towards The Growth Of Pakcoy Mustard (Brassica Rapa L) and Dumbo Catfish (Clarias Gariepinus) in Aquaponic System - Oktaviana Elsa Dewi; Sapto Andriyono; Mochammad Amin Alamsjah (Universitas Airlangga, 2020)
Aquaponics is a technology that combines the cultivation of vegetable production and fish farming. The aquaponics technology also to fertilization to give nutrients to the plant to support of survival. In facts, fertilization done to plants is located on land. Fertilizing the plants that live in the waters are still very rare, because the waters as a growing medium that is considered to always provide sufficient nutrients for plant growth. In this research, using biofertilizer Euchema cottonii of seaweed. The advantages of biofertilizer seaweed is to have the content of macro and micro nutrients are complete. It also contains substances hyper Grow (PGR) plant (auxin, cytokinin, gibberellin, abisat acid and ethylene).In this research to determine the effect of biofertilizer products of seaweed (E. cottonii) commercial on the growth of dumbo catfish (C. gariepinus) and pakcoy mustard (B. rapa L) on aquaponics system. The design of experiments in this research using a completely randomized design (CRD) with 5 treatments and 4 replications. The treatment used is fertilizer